Relações étnico-raciais e educação: políticas antirracistas no município de Cariacica - Oliveira, Thaynara Silva (2019)
The objective of this research is to understand how the appreciation of ethnic and racial relations, culture and African and Afro-Brazilian history, materialized in public policies in the city of Cariacica. This occurs from the changes in the Law of Guidelines and Bases of National Education in 1996 and, subsequently, from Law 10.639 / 2003 and 11.645 / 2008. To this end, the period will analyze the policies and initiatives implemented in the city between 2003 and 2019. It is a bibliographic and documentary research. It consists of analyzing documents in perspective of ethnic-racial issues. It is based on the concepts of Culture and Identity (EAGLETON, HALL, BRANDÃO, among others), focusing on issues related to ethnic-racial relations (ALMADA, ALMEIDA, GOMES, MUNANGA, SISS, SCHWARCZ, among others) to scale the theme. Without context of public policies aimed at Education. Analyze laws, guidelines and other municipal and national documents that will fit into the affirmative policies of ethnic and racial issues in Cariacica-ES. As an analysis pointed to the importance of the institution of policies and its implementation. The study makes it possible to say that the policies considered represent the struggle of the Caryatic black movements and their study becomes important due to their consonance with the policies that are taking place at the national level. At the same time, reinforce the need to promote or access information related to these devices, copyright essential to the black population